Genetic diversity and population structure analysis of Colletotrichum capsici isolates using SRAP and URP markers - Kumar, Pardeep; Dubey, S C; Akhtar, Jameel; Kiran, Raj; Nair, Krishna; Bhati, Heena (Indian Journal of Plant Protection, 2020)
Colletotrichum capsici causing anthracnose is a major quality and yield-limiting factor of chilli in India and elsewhere. The present study was undertaken to determine genetic variability and population structure among 12 indigenous and one exotic isolate of C. capsici using SRAP and URP markers. Out of 15, each of SRAP and URP markers screened, 13 SRAP and 10 URP markers gave reproducible banding pattern. At a similarity coefficient of 0.77, thirteen isolates of C. capsici were classified into three major clusters based on unweighted paired-grouping method with arithmetic averages of NTSYSpc and the Bayesian analysis of population structure. The exotic isolates from USA grouped in cluster III along with two indigenous isolates from Bagalkot and Parbhani. The various genetic diversity parameters like percent polymorphism, number of different alleles, number of effective alleles, expected heterozygosity, polymorphism information content, Shannon’s information index, resolution power, effective multiplex ratio and marker index were studied, which revealed that there is genetic variability with three different populations among isolates in Karnataka region only. Therefore, the information generated in the present study could be used for devising breeding strategy for developing disease resistant varieties at regional level.